Using Some Promising Insecticides as A Management Tool Against The Major Sucking Pests of Country Bean - Md. Abdur Razzak Choudhury; Md. Abdul Maleque; Nazmin Nahar Mily; Ahasan Ullah Khan (Journal of Multidisciplinary Applied Natural Science, 2023)
An experiment has been conducted to know the efficiency of some promising pyrethroids and bio-rational insecticides for controlling the major sucking pests of country beans under field conditions during the winter season September 2020 – March 2021. The different treatments were Cypermethrin 10 EC (T1), Lambda-Cyhalothrin 2.5 EC (T2), Emamectin benzoate 5 SG (T3), Abamectin 1.8 EC (T4), Spinosad 45 SC (T5), and untreated control (T6). The rate of leaf infestation at the lower, middle, and top stages of country bean ranged from 8.82–17.78, 13.89–36.39, and 13.72–33.33% in T5treated and untreated control plots, respectively. The rate of shoot infestation at the middle and top stages of country bean ranged from 18.67–34.33 and 17.00–39.27% in T5 treated and untreated control plots, individually. The lowest and highest inflorescence infestation of 29.15% and 46.67% was recorded in T5 treated and untreated control plots, separately.The lowest fruit infestation of 8.84% by number and 8.32% by weight was recorded in the treated plot T5. The rate of reduction of pod infestation over control was 48.58, 24.02, 23.39, 21.81, and 19.92% by number and 73.53, 61.76, 58.82, 52.94, and 41.18% by weight in the treated plot T5, T4, T1, T3, and T2, respectively. The yield in different treatments ranged from 1.35-2.50 t ha-1. The highest adjusted net return and BCR of Tk. 52220.00 and 2.42, respectively were obtained from T2 treated plots. The second highest BCR of 2.16 was calculated from T4 treated plot. The lowest BCR of 1.05 was found in T2 treated plot. The treatments T5, T4, and T3 were effective to suppress the major sucking pests of the country bean.